Improvement of the electron transfer rate in Shewanella oneidensis MR-1 using a tailored periplasmic protein composition - Delgado, Veronica Palma (2019)
Periplasmic c-type cytochromes are essential for the electron transport between the cytoplasmic membrane bound menquinol oxidase CymA and the terminal ferric iron reductase MtrABC in the outer membrane of Shewanella oneidensis cells. Either STC or FccA are necessary for periplasmic electron transfer. We followed the hypothesis that the elimination of potential competing reactions in the periplasm and the simultaneous overexpression of STC (cctA)could lead to an accelerated electron transfer to the cell surface. The genes nrfA, ccpA, napB and napA were replaced by cctA. This led to a 1.7-fold increased ferric iron reduction rate and a 23% higher current generation in a bioelectrochemical system. Moreover, the quadruple mutant had a higher periplasmic flavin content. Further deletion of fccA and its replacement by cctA resulted in a strain with ferric iron reduction rates similar to the wild type and a lower concentration of periplasmic flavin compared to the quadruple mutant. A transcriptomic analysis revealed that the quadruple mutant had a 3.7-fold higher cctA expression which could not be further increased by the replacement of fccA. This work indicates that a synthetic adaptation of Shewanella towards extracellular respiration holds potential for increased respiratory rates and consequently higher current densities.